LONG-TERM APPLICATION EFFECTS OF ORGANIC AND CHEMICAL FERTILIZERS ON SOIL HEALTH AND PRODUCTIVITY OF TARAMIRA (ERUCA SATIVA L.) UNDER RAINFED CONDITIONS - R. S. Noor; Z. Wang; M. Umair; M. Ameen; M. A. Misaal; Y. Sun1 (Journal of Animal and Plant Sciences, 2020)
Intensive cultivation system suffers from production fatigue caused by declining soil organic matter, multi-nutrient deficiencies and diminishing factor productivity. A long term field experiment (2015-16 to 2018-19) was conducted to determine the impact of sole and integrated application of farm yard manure (FYM) and Chemical fertilizer (RDF); sole organic fertilizer (OF), chemical fertilizers (RDF) and potassium phosphate (RPK) while half dose of chemical fertilizer with full and half dose of organic fertilizer (HDF+OF and HDF+HOF) as well as the RPK with nitrogen foliar (RPK+NF) as integrated fertilizer options and controlled (CK) on soil properties, plant growth characteristics and crop productivity in completely randomized design (CRD). The long-term fertilizer results revealed that the organic and integrated fertilizer options significantly enhanced plant growth characteristics, yield and seed quality. The yield trends were positive (p ≤ 0.05) under all organic fertilizers but, integrated fertilizer (HDF+OF) significantly increased plant height, branches/plant, root length, disease resistance, siliqua/plant, siliqua length, seeds/siliqua, 1000 seed weight, and seed yield. The annual seed yield obtained from the field fertilized with (HDF+OF) were 10, 12, 18 and 22% more than that of the field fertilized with chemical fertilizer, respectively during four years of study. Oil, protein, glucosinolates and acids contents in seed also increased with organic fertilizer. Eruca plant leaves fertilized with (HDF+OF) contained higher bioactive substance concentrations as L-ascorbic acid (119.36±0.48 mg 100g-1 FM), chlorophyll (0.73±0.01 mg 100g-1 FM), glucosinolates (17.18±0.09 µmol g-1 DM), flavonoid (0.90±0.00 g 100g-1 DM) and essential oil (0.16±0.00 ml 100g-1 DM). Integrated fertilizers proved to be more beneficial due to improved nutritional contents and energy values in eruca sativa leaves. The senescence was effectively delayed throughout the storage period of 0 and 5°C. Compared with chemical fertilizers, the organic fertilizers significantly improved bulk density and soil chemical health (SOC, NO3-N, NH4-N, P, K, S, Zn contents).
Keywords: Eruca sativa L.; fertilizer options; plant development; seed yield & quality; bioactive substance & nutritional values; leave storage performance and soil chemical health